Pentingnya Peran Bahasa dalam Pendidikan Anak Usia Dini (PAUD) (PIAUD IAIN Kudus, 2014)
Language is the tool of human interaction to convey a message oridea in fikiranya. It is an extraordinary thing if they were involved in earlychildhood education teaching materials capable of delivering them well. Thestudents of this age are vulnerable times for them. If they are too restrained, itwill hinder their psychological development, and vice versa if they are also notbe allowed, it will stabilize their development. Therefore at this time they stillplay, seek attention, and look for praise. Then an educator should be able toconvey recording a language pack.